Kajian Penggunaan dan Manfaat Pusat Terapi dan Pendidikan Anak Berkebutuhan Khusus di Surabaya - Ambarwati, Catherina Novitas; Darmiwati, Theresia Ratna; Putra, Heristama Anugerah (Darma Cendika Catholic University, 2022)
Children with special needs are children who need special handling due to developmental disorders and children's abnormalities. Children with emotional and behavioral disorders as well as intellectual disorders need longer handling. Surabaya is a metropolitan city that has quite a number of children with special needs, namely in 2013 it reached 813 people and increased in 2014 by 907 people, while in 2015 it decreased but not significantly to 904 people. Surabaya still does not have a place to facilitate all types of children with special needs, starting from the land, security and comfort of the design, as well as the proper function of space for the Children with special needs itself. Therapy and education is one way to deal with children with special needs. Whereas in the field of education contained in the 1945 Constitution article 31 paragraph 1 and Law no 20 of 2003 concerning the National Education system which states that children with special needs are entitled to also have the same opportunities as other children in education. The design method uses the search method. design ideas, problem identification, design goals, data collection, design data analysis, design concepts, and design. The location of the Children with special needs Therapy and Education Center design was on Mayjend Sungkono Street, Surabaya with an area of ​​11,520 m².